The dynamics of sediment transport off the coast of Cavite - Doruelo, Julius Caesar S. (2000)
A multi-method investigation of the dynamis of sediment transport in the offshore and nearshore regions of Cavite was conducted. granulometric analysis of sediments was done to determine offshore sediment transport patterns. nearshore sedimentation was modeled by integrating wave refraction data with records of bathymetric and shoreline changes. Time-series maps and lonshore current model derived from wave refraction diagrams were also use to correlate long-term shoreline changes with net longshore transport. Sediment distributions showed that the Cavite offshore consists of two distinct sub-environments demarcated by the San Nicolas Shoal. the extremely poorly sorted and positively skewed muds indicate low-energy hydrodynamic conditions in the area north of the shoal whereas the moderately to poorly sorted and negatively skewed sands to the south, signify an environment exposed to strong waves or currents. the textual trends further showed that the sediment transport patterns in these two regions are highly varaible. North of the shoal, sediments are transported to the southeast, east, and northeast or seaward in certain area. The sediment transport pathways in the northern and southern portions of the Cavite offshore, respectively converge on the norhteastern and southwestern flanks of the San Nicolas Shoal. Tide- and wind-driven circulation models and wave refraction simulations were invoked as hydrodynamic forcing for the offshore sedimentation model. The Cavite Spit is direct evidence of the net longshore drift to the northeast. Integration of field accounts with data on shoreline change and the inferred longshore model derived from the wave refraction diagrams further suggested that the longshore currents correspond with the seasonal wind regime. Strong northeast-directed longshore currents, which bring huge amounts of sands, are generayed by thr southwest monsoons but relatively weaker southwestward currents are produced during the northelies or northeasterlies. Net longshore sedmient transport is determined to be northeastward. Moreover, it was shown that the long-term shoreline retreat in the Cavite coastline could be attributed to the general transport of sediments to the northeast by the inferred longshore currents. Despite the bathymetric deepening, possibly dur to the loss of bottom sedmients, the shoreface profiles generally maintained an equilibrium shape that translated landward and caused the shoreline to retreat through time. This signifies the correlation between shoreline transgression and bathymetric deepening. Several other mechanisms couls explain this correlation bu these were not wholly considered in this study. Nonetheless, it was shown that changes in the nearshore and offshore topography could potentially influence shoreline position. In all, the integrated approach utilized in this research proved effective in modeling the dynamics of sedimentation off the Cavite offshore. Apart from supplying baseline data for further studies on sediment transport in the southeastern coasts of Manila bay, this study also set an example upon which future stduies on coastal sedimentation could be based. Most importantly, it has extended our understanding of the dynamic coupling of the geologic, geomorphic and oceanographic factors that influence sediment transport off the coast of Cavite.
"August 2000."
Vita.
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Thesis (M.S. Geology)--University of the Philippines Diliman.
Keywords: Sediment transport -- Philippines -- Cavite; Sedimentation and deposition -- Philippines -- Cavite